Gadofosveset - a blood pool contrast agent used with MRI to detect obscure gastrointestinal Bleeding: a case report - Jacobi, Björn (The American journal of gastroenterology, 2012)
Gadofosveset - A Blood Pool Contrast Agent Used with MRI to Detect Obscure Gastrointestinal Bleeding: A Case Report